Pesantren and Disability: the Dynamics of Islamic Boarding School in Accommodating Children with Disabilities - Ghufron, M. Nur; Nasir, Amin (LPPM IAIN Kudus, 2019)
Islamic Boarding School is one of the Islamic educational institutions in Indonesia, Islamic boarding school is a religious education institution that has its distinctiveness and is different from other education. Education in Islam, education, da’wah, community development, and other similar education. In general, Islamic boarding schools accept normal Santri in terms of ability. However, there are Islamic boarding schools that only accept students who have special needs. The purpose of this study was to study how disability education in al-Achsaniyyah Islamic Boarding School. This study used descriptive qualitative method. This study involved six informants, consisting of one main informant, and five supporting informants who worked on supplementing the data. The selection of informants is based on purposive sampling. Data exploration was carried out by in-depth interviews, non-participant observation, and field notes. The validity of the study was carried out by the method of data triangulation, namely by checking the facts by comparing them with various sources, methods, and theories. The results showed that al-Achsaniyyah Islamic Boarding School is a special boarding school for people with disabilities located in Kudus, Central Java. Like other huts, Pondok al-Achsaniyyah Kudus also has elements in the form of Kyai, dormitories, mosques as centers of worship, schools and the presence of Santri. It’s just that students in al-Achsaniyyah Kudus Islamic Boarding School are autistic.